A REVIEW OF DATA GOVERNANCE MATURITY LEVEL IN HIGHER EDUCATION - Hanung Nindito Prasetyo (Jurnal Ilmiah Teknologi Infomasi Terapan, 2016)
Data governance in organization is unique. Every organization has a form of data governance in accordance with their respective needs. In some literature most of the industry, build data governance program based on the needs of data quality in achieving the company's goals. Some research have shown that data quality management is the foundation of data governance development in the industry. Although the data quality management is an important foundation, but in the development of the industry show the form of data governance that vary according to the needs and interests of the company. To see the effectiveness that data governance has been implemented well in an organization, it is needed a measurement mechanism of maturity level. However, to determine whether the measurements were carried out in accordance with the organization's goals, it will be require a clear base in determining the dimensions of the measurement. This research tried to describe the dimensions of which will be used during the activity measurement data governance maturity level within an organization. The measurement model used as a reference is the IBM data governance and DAMA International.